James Madison - Wills, Garry 1934- (The American presidents series, 2002)
In this examination of the life of a founding father, renowned historian Wills takes a fresh look at the life of James Madison, from his rise to prominence in the colonies through his role in the creation of the Articles of Confederation and the first Constitutional Congress.